2016
DOI: 10.2118/168153-pa
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of the Effects of Condensate Banking: A Critical Review

Abstract: With production from gas/condensate reservoirs, the flowing bottomhole pressure of the production well decreases. When the flowing bottomhole pressure decreases below the dewpoint, condensate accumulates near the wellbore region and forms a condensate bank. This results in a loss of productivity of both gas and condensate, which becomes more serious in intermediate-and low-permeability gas/condensate reservoirs, where the condensate bank reduces both the gas permeability and the well productivity.Several techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 121 publications
(168 reference statements)
0
52
0
1
Order By: Relevance
“…Based on this complex phenomenon, a lot of studies have been approached to study on the best method in enhancing the hydrocarbon recovery [7][8][9][10][11][12]. One of those techniques is gas flooding.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this complex phenomenon, a lot of studies have been approached to study on the best method in enhancing the hydrocarbon recovery [7][8][9][10][11][12]. One of those techniques is gas flooding.…”
Section: Introductionmentioning
confidence: 99%
“…In a gas condensate reservoir, the reduction of reservoir pressure results in liquid drop-out, which can accumulate around the production well and create a condensate blockage. The condensate bank reduces the effective permeability to gas, and then, the total gas production will be dramatically decreased [29]. Injection of thermochemical fluids into gas condensate reservoirs can result in enhancing hydrocarbon production utilizing several mechanisms.…”
Section: Gas Production Improvementmentioning
confidence: 99%
“…Therefore, the condensate liquid will accumulate around the production well and result in reducing the total gas production below the economic limits [26]. Different treatments are applied to remove the accumulated liquids and improve the gas production [27][28][29]. Gas and chemical injections are used to increase the pressure and change the phase behavior of liquid condensate; then, it can be easily produced through the production well.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that, injection of carbon dioxide is recommended over water flooding for removing the condensate damage and improving the gas deliverability. The problem of CO 2 injection is that it is a temporary solution and has to be repeated frequently in the field in addition to the supply limitations of CO 2 in some areas [4]. In addition, the infrastructure required at the surface to handle CO 2 injection makes it expensive to apply CO 2 injection for condensate removal.…”
Section: Introductionmentioning
confidence: 99%